Investigating the Political Base of Indonesian Middle Class: A Comparative Study (Universitas Negeri Semarang, 2017)
This article aims at analyzing the political base in the case of Indonesian middle class. It is essential to note that many multi-interpretation understandings to define terminology of Indonesian middle class. The definition of Indonesian middle class still undermines as “middle group” which is related to new rich people. Based on comparative analyzes, the emergence of Indonesia middle class have been separated with western middle class. In western case, middle class has possessed stable economic and politics material sources independently toward the state. The situation is what transforms the middle class as presser to the states and interest group. It can be said that both processes of the deepening of democratization and economic strength have been encouraged by middle class. In the Indonesian experience, it has been shown that Indonesian middle class keep up mutual relationship to the state. In other words, Indonesian middle class have entered elite power structure. However, in the current time, Indonesian middle class in post-reformation era shows the emergence of political awareness to guard democracy justly. This article will elaborate deeply political basis of Indonesian middle class.